2012
DOI: 10.1007/s13365-011-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased cortical expression of FK506 binding protein-51 in HIV-associated neurocognitive disorders

Abstract: FK506 binding protein (FKBP)-51 and FKBP52 act as molecular chaperones to control glucocorticoid receptor (GR) sensitivity. Dysregulation of proteins involved in GR-mediated signaling can lead to maladaptive stress response and aging-related cognitive decline. As HIV infection is related to chronic stress, we hypothesized that altered cortical expression of these proteins was associated with HIV-associated neurocognitive disorders (HAND). We used quantitative immunohistochemistry to assess expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The sections were incubated with 90% formic acid (5 min for Aβ staining) or 10 mM sodium citrate/0.05% Tween 20 buffer (pH 6) in 121°C autoclave (20 min for p-Tau staining). Immunohistochemical signals were developed using species-appropriate ImmPRESS ™ anti-IgG (peroxidase) polymer detection kits (Vector Laboratories, Burlingame, CA, USA) and diaminobenzidine (ImmPACT ™ DAB peroxidase substrate, Vector Laboratories), as previously described [31]. The sections were counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were incubated with 90% formic acid (5 min for Aβ staining) or 10 mM sodium citrate/0.05% Tween 20 buffer (pH 6) in 121°C autoclave (20 min for p-Tau staining). Immunohistochemical signals were developed using species-appropriate ImmPRESS ™ anti-IgG (peroxidase) polymer detection kits (Vector Laboratories, Burlingame, CA, USA) and diaminobenzidine (ImmPACT ™ DAB peroxidase substrate, Vector Laboratories), as previously described [31]. The sections were counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, expression of FKBP5 and its genetic variations have been linked to a number of psychiatric conditions involving HPA axis dysfunction including depression (Menke et al 2013), post-traumatic stress disorder (Klengel et al 2013), and chronic stress (Hartmann et al 2012). In addition to the established influence of FKBP5 on the GR, FKBP5 has been shown to play a role in HIV-associated cognitive deficits in PLWH (Soontornniyomkij et al 2012, Tatro et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2009a). More recently, a study showed increased cortical expression of FKBP51 in the mid‐frontal gyrus of 55 HIV‐infected subjects free of cerebral opportunistic diseases whereas no significant alterations were observed for GR or FKBP52 (Soontornniyomkij et al. 2012), which would represent the negative feedback to reduce GR sensitivity in the setting of chronic stress‐induced elevation of GR‐mediated signaling inherent in HIV infection and could be related to maladaptive stress response and HIV‐associated neurocognitive disorders.…”
Section: Depressive Disorders Related To Hiv Infectionmentioning
confidence: 99%